Root injury detection by impedance loss factor and hydraulic conductance of apple (Malus domestica), blackcurrant (Ribes nigrum) and blueberry (Vaccinium corymbosum) nursery plants - Wu, Dongxia; Sun, Jian; Silvennoinen, Raimo; Repo, Tapani (Elsevier, 2024)
In order to avoid winter damage, freezer storage has become a common practice in production of nursery plants in boreal zones. Previously, winter storage temperature of −3 °C was appropriate for the aboveground parts of apple, blueberry and blackcurrant nursery plants but it remained unknown whether it is optimal for root systems too. Therefore, we examined the effect of different treatment temperatures of 3, −3, −7, −10 °C for five to six weeks on root damage of two cultivars of apple (Malus domestica), three cultivars of blackcurrant (Ribes nigrum), and three cultivars of blueberry (Vaccinium corymbosum). Root damage was assessed by the impedance loss factor (δ) and the reverse-flow hydraulic conductance (Kr) of the roots. In apple, the proper storage temperature for roots during winter storage is −3 °C. However, the appropriate storage temperature for root systems of blueberry and blackcurrant depends on the cultivar. In addition, our results demonstrate the potential of the classification analysis of impedance spectra in identifying the appropriate storage conditions for different species. This approach can provide a rapid way to assess the root damage caused by low temperature and help to optimize the storage conditions for different species and cultivars. Further research is needed to investigate mechanisms underlying the observed effects and to develop practical applications based on these findings.
Keywords: Frost hardiness; Woody horticulture plants; Hydraulic conductance; Impedance loss factor